Determination of probability distribution for data on rainfalland flood levels in Bangladesh - Mohammad, Ferdows, Dr.; OTA, Masahiro; Roushan, Jahan; MNA, Bhuiyan; Md. Mubarak, Hossain, Prof. (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/